TREATMENT OF ACTIVATED CARBON TO ENHANCE CATALYTIC ACTIVITY FOR REDUCTION OF NITRIC-OXIDE WITH AMMONIA - KU, BJ; LEE, JK; PARK, D; RHEE, HK (AMER CHEMICAL SOC, 1994)
Catalytic activity of activated carbon treated with various techniques was examined in a fixed bed reactor for the reduction of nitric oxide with ammonia at 150-degrees-C. Activated carbon derived from coconut shell impregnated with an aqueous solution of ammonium sulfate, further treated with sulfuric acid, dried at 120-degrees-C, and then heated in an inert gas stream at 400-degrees-C, showed the highest catalytic activity within the range of experimental conditions. The enhancement of catalytic activity of modified activated carbon could be attributed to the increase in the amount of oxygen functional groups which increased the adsorption site for ammonia. Catalytic activity of activated carbons depended on the surface area and the oxygen content as well.
Keywords: CHARS